Instilling Participatory Planning in Disaster Resilience Measures: Recovery of Tsunami-affected Communities in Banda Aceh, Indonesia - Grace Yuswita Harahap (Budapest International Research in Exact Sciences (BirEx) Journal, 2020)
Strategically, if community improvement is to become an important priority in post-disaster recovery efforts, then the spectrum of recovery must be widened to instill disaster resilience measures. In fact, to achieve this goal all efforts should be participatory in the approaches and adopt empowerment as a strategic objective. In post-tsunami areas in Aceh, Indonesia, the Village Planning Guidelines are designed, not only to rebuild the village physically, but also to instill disaster response measures where the ultimate goal is to ensure that the community is self-reliant, highly-motivated and action-oriented. Significantly, the inculcation of such positive attributes in the community will prepare them well for disaster mitigation in the future; in such way that the community enable to carry out effective and appropriate reconstruction stages in comprehensive recovery process. Thus, this study evaluates whether chosen participatory approach in village planning process is capable to empower the affected-community in Banda Aceh. Through survey and personal interview of forty respondents from four most-devastated villages, answers for twenty-two questions derived from five variables as criteria of effective facilitation process, resulted that the community agreed facilitation approaches succeeded to encourage the affected-community to involve actively in planning process. However, answers for twelve questions from three variables of effective empowerment process showed that the community gained empowerment simply to an extent. This is a confirmation to general opinion that facilitation needs longer time in its process to empower community. For this reason, further research is expected to develop specific post-disaster participatory approaches in effort to evolve the capability-development level of affected-community.